Alfred Hitchcock presents. Season two [videorecording (DVD)] - Hitchcock, Alfred, 1899-1980; Hitchcock, Alfred, 1899-1980; Tandy, Jessica; Cronyn, Hume; Morrow, Vic, 1931-1982; Silva, Henry, 1928-; York, Dick, 1928-1992; Rains, Claude, 1889-1967; Gounod, Charles, 1818-1893 (Universal classic television., 2006)
Alfred Hitchcock, master of suspense, always started out his show with the line 'Good Evening.' Loaded with twists, turns, and things that go bump in the night, view this storyteller's classic tales with some of the biggest names in showbiz.